Obtenção e caracterização de carvão ativado a partir de resíduos de casca de castanha do pará (Bertholletia excelsa) e sua aplicação na adsorção de fenol - Silva, Maria Caroline Ferreira da (2023)
The water contamination by organic compounds can cause damage to the environment and human beings. Adsorption is a promising process for removing these pollutants. Agricultural residues are a great alternative as precursors in the production of adsorbents, as is the case of the Brazil nut shell (Bertholletia excelsa), where in this study two activated carbons (AC11 and AC 105) were obtained, using chemical activation with KOH, in proportions of 1:1 and 1:0.5 respectively. The coals were characterized and applied as adsorbents for phenol removal. Characterization was performed using techniques such as SEM, FTIR, BET, TGA, and XRD. The characterization data showed that both materials showed similar properties, with AC11 exhibiting a slightly larger specific surface area and several rounded cavities along the surface (332.2 m2 g −¹ ) than AC105 (314.3 m2 g -¹ ). The kinetic study showed that AC11 reached process equilibrium faster than AC105. Adsorption maxima were 55.16 and 68.52 mg g –¹ for AC105 and AC11, respectively. The application of the materials in the treatment of a simulated industrial effluent showed removal efficiencies of 28.05% and 48.20% for AC105 and AC11, respectively. Therefore, through the adsorption results, AC11 was more efficient when compared to AC105. This place in better conditions, with regard to phenol adsorption, was favored in the adsorbent dosage of 0.75 g L -¹ and pH 6. The kinetic investigation revealed that the system reached equilibrium in about 180 minutes and the kinetic curves represented by the Elovich model. Equilibrium isotherms were represented by the Sips model. Furthermore, increasing the temperature from 25 to 55 °C favored phenol adsorption, increasing the value of the maximum adsorption capacity (qs) from 82.99 to 99.02 mg g −¹. According to the estimated thermodynamic parameters, the adsorption was spontaneous, favorable, endothermic, and governed by physical interactions. Therefore, the bark of the Brazil nut proved to be a good material for obtaining activated carbon efficiently in removing phenol.